Being a woman judge in Turkish judicial culture - Kalem, Seda (Routledge Journals, Taylor & Francis Ltd, 2020)
This study is a feminist exploration of how gender influences the professional and social lives of women judges in Turkey. I asked women judges from lower courts to talk about their professional journey to explore if and how gender emerges as a category that makes sense to them. Gender was sometimes more visible in the form of a success story of playing along men's rules, or in memories of struggling to balance work and family; while other times it was more implicit in narratives on meeting expectations, failing expectations, ignoring expectations. All in all, these narratives attest to the gendered hierarchies and instances of institutional sexism in what is considered a masculine profession. They also reveal the prevalence of a particularly conservative and patriarchal culture upon the ways in which these inequalities and disadvantages are experienced by women judges in Turkey.